Technological co-operation and contribution among OIC members with special reference to Bangladesh and Iraq - Md. Lutful Huq, Nayeem; Shuriye, Abdi Omar (Mediterranean Center of Social and Educational Research, 2013)
Science and technology is a pair of the most prominent words to day. To understand the natural systems is Science and technology is the way to control or to implement it for ourselves. Scientists set a goal to attain something, which ordinary people could hardly imagine, and then work to reach there in a very rational and methodical approach. Thus in combination of science and technology we get upgraded systems for the welfare of humanity. In present days, technology is the key indicator for development. While cooperation or collaboration, among the societies, is an essential mean for development. Scientific and technical journal articles are one of the most important science and technology indicators. This paper discusses to major aspects of development; cooperation and contribution. Firstly, the present condition of science and technology and the cooperation in these fields among the members of IOC is discussed here. Where it is found that the most of the members are lagging behind the developed world and more alarming problem is there is a very little cooperative effort among the OIC members themselves. Due to not having adequate knowledge, technology, and support sometimes, they are bound to collaborate more with non-OIC countries than the members do. In spite of that, there is still a huge opportunity to overcome these problems as the OIC members have been blessed by the natural resources and thus have the financial support to overcome any obstacle. To do so, the members need to be more cooperative to each other in all sectors of research and development. They need to remain united as a single body to uphold the brotherhood. Secondly, good contribution to the field of science and technology indicates the smart society of the present time. The advancement in these sectors is an indication of living standard of the people. Here, the roles of two countries, Bangladesh and Iraq, in the field of science and technology, have been discussed. Both the countries have a long history, in different names under different era of kingship. Bangladesh has a large population, near about 146.6 million, of which almost 89% is Muslim (BBS, 2011), so as a member of OIC she holds of great importance in South Asia. It is remarked that the ancient Bengal was neither developed nor focused as a future technological base by any of the rulers. However, in last two decades she is been showing a consistently rising pattern in these fields especially in agriculture and IT sectors. However, Bangladesh is still far away to have a standard infrastructure for R&D in science and technology. On the other hand, the land of Iraq has been the mother of world’s first civilization and as a Muslim country; Iraq has a glorious history of about thousand years in almost all sectors of development. Nevertheless, in the last few decades, the consecutive involvement in war, killed hundreds of scientist, and destroyed many research facilities, institutions, universities, which eventually destroyed the knowledge base and led Iraq almost to a blind alley. Now it is inevitable for her to reconcile and fight back.